Toxicogenomic Profiling of 28 Nanomaterials in Mouse Airways. Issue 10 (8th March 2021) - Kinaret, Pia A. S.; Ndika, Joseph; Ilves, Marit; Wolff, Henrik; Vales, Gerard; Norppa, Hannu; Savolainen, Kai; Skoog, Tiina; Kere, Juha; Moya, Sergio; Handy, Richard D.; Karisola, Piia; et al.
Abstract: Toxicogenomics opens novel opportunities for hazard assessment by utilizing computational methods to map molecular events and biological processes. In this study, the transcriptomic and immunopathological changes associated with airway exposure to a total of 28 engineered nanomaterials (ENM) are investigated. The ENM are selected to have different core (Ag, Au, TiO2, CuO, nanodiamond, and multiwalled carbon nanotubes) and surface chemistries (COOH, NH2, or polyethylene glycosylation (PEG)). Additionally, ENM with variations in either size (Au) or shape (TiO2 ) are included. Mice are exposed to 10 µg of ENM by oropharyngeal aspiration for 4 consecutive days, followed by extensive histological/cytological analyses and transcriptomic characterization of lung tissue. The results demonstrate that transcriptomic alterations are correlated with the inflammatory cell infiltrate in the lungs. Surface modification has varying effects on the airways with amination rendering the strongest inflammatory response, while PEGylation suppresses toxicity. However, toxicological responses are also dependent on ENM core chemistry. In addition to ENM‐specific transcriptional changes, a subset of 50 shared differentially expressed genes is also highlighted that cluster these ENM according to their toxicity. This study provides the largest in vivo data set currently available and as such provides valuable information to be utilized in developing predictive models for ENM toxicity. Abstract : C57BL/6 mice are exposed by oropharyngeal aspiration to 28 different engineered nanomaterials (ENM). Histological and cytological evaluation together with transcriptomics analyses reveals the important effect of surface functionalization (amination, carboxylation, or pegylation) as well as the significant role of the ENM core chemistry.